Saturated And Unsaturated Fatty Acids Contents Analysis in Nasi Padang Chicken Gulai and Nasi Kandar Chicken Curry - Hashim Fadzil Ariffin; Laili Hidayati; Afellia Febrianti (Universitas Negeri Malang, 2022)
Nasi Padang chicken gulai and Nasi Kandar chicken curry are traditional dishes made with coconut milk, thick sauce, and creamy gravy due to their lengthy processing. Chicken curry has a slightly spicy flavor, a reddish yellow sauce color, and a stronger aroma due to the addition of spices and herbs during the cooking process. This study aims to determine the saturated fatty acid and unsaturated fatty acid content in chicken gulai and chicken curry. The data of chicken gulai’s and chicken curry’s fatty acid was collected using Shimadzu’s GC (Gas Chromatography) instrument. As this study used an experimental research design, then T-test was employed in the data analysis process. The analysis results indicated that the saturated fatty acid content of chicken gulai and chicken curry was identical, as both were prepared using the same heated coconut milk. However, for an extended period, the saturated fatty acid content of chicken gulai and chicken curry increased, while the unsaturated fatty acid content remained unchanged, owing to the high spice content from some ingredients used in their processing. Besides, essential oils were also found in spices.